(untitled) (Journal of the College of Basic Education, 2025)
This research aims to identify The role of the Stepanz model in students’ acquisition of chemical concepts. The research used the descriptive analytical method, where data and information were collected through a questionnaire tool, which targeted a sample of chemistry teachers in the Rusafa district. The sample included 236 teachers, male and female, in addition to a reconnaissance sample of 30 male and female teachers. The questionnaire consisted of 31 items distributed across three axes: 1- The first axis: The role of Stepanz model from the perspective of chemistry teachers in students’ acquisition of chemical concepts. 2- The second axis: The effectiveness of the Stepanz model in confronting and exploring misconceptions in chemistry. The validity and reliability of the research tools and the internal consistency of the questionnaire items were verified. The results showed that there were statistically significant differences between the averages of the sample members regarding the existence of a correlation between the use of the Stepanz model and the acquisition of chemical concepts in terms of gender, age, years of experience, and educational level of the sample members.